(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines aspects related to the author’s beliefs, translated from Persian, through the thoughts expressed in the preface to the work "Mir’atus Salikin" written for the Tariqat by the Sufi mystic Mirbabo Naqshbandi, who contributed to the development of the Naqshbandi order in India.